Thyroid-Type Carcinomas of Ovarian Origin (Malignant Struma Ovarii). Issue 5 (September 2016) - Hall, Allison H.S.; Komforti, Miglena K.; Jiang, Sara; Robboy, Stanley J.
Abstract : Abstract: Struma ovarii is a monodermal variant of mature teratoma in which thyroid tissue predominates. Rarely, struma ovarii undergoes malignant transformation. Malignant struma ovarii (MSO) includes tumor types seen in the eutopic thyroid, such as papillary thyroid carcinoma (both the classical type and the follicular variant) and follicular carcinoma. Sometimes, the strumal component arises intertwined with carcinoid, the combination designated strumal carcinoid tumor. These tumors have histologic, immunohistochemical, and molecular features similar to their counterparts that arise in the thyroid itself. Despite having histologic features of malignancy, few MSO recur or metastasize. There are also occasional struma ovarii that lack histologic features of malignancy but behave in a clinically malignant fashion. Malignant struma ovarii in general has an excellent prognosis with high rates of long-term survival. Even in patients with extraovarian spread, the disease often has a protracted course. Because recurrences commonly appear only many years after the initial diagnosis and because histologic features do not accurately predict tumor behavior, long-term follow up is required for all patients with MSO.